Customer relationship officer’s engagement in learning & development department of BRAC Bank Limited - Nayeem, Fabiha Binte (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.